2016
DOI: 10.5546/aap.2016.eng.101
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between sport and physical activity and alcohol consumption among adolescents students in Murcia (Spain)

Abstract: Introduction. Sports and physical activity are major components of a healthy lifestyle. The objective of this study was to analyze the relationship between sport and physical activity and alcohol consumption among adolescent students based on gender. Population and methods. Descriptive, crosssectional, comparative study conducted in adolescent students (aged between 14 and 17 years old) from the Region of Murcia in 2014. Sport and physical activity was assessed using a validated, adapted survey that included b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 16 publications
0
13
0
1
Order By: Relevance
“…Positive effects are achieved primarily through physical activity, which is the main part of most sports. Many secondary effects of sport also bring health benefits, such as psychosocial development of both young [1] and old [2], personal development [3], later onset, and less consumption of alcohol [4,5]. Finally, those who play sports have a higher level of physical activity later in life [6], and through sport, knowledge of nutrition, exercise, and health can be developed [7].…”
Section: Introductionmentioning
confidence: 99%
“…Positive effects are achieved primarily through physical activity, which is the main part of most sports. Many secondary effects of sport also bring health benefits, such as psychosocial development of both young [1] and old [2], personal development [3], later onset, and less consumption of alcohol [4,5]. Finally, those who play sports have a higher level of physical activity later in life [6], and through sport, knowledge of nutrition, exercise, and health can be developed [7].…”
Section: Introductionmentioning
confidence: 99%
“…Improper behaviors such as drinking, smoking, and drug use are the factors that make the physical health as well as mental health of the youth vulnerable. López Villalba et al (2016) reported that physical activity positively correlates with low alcohol consumption for boys and girls in adolescence, and the result was higher in male youth than female youth. In addition, physical activity is also used to control smoking.…”
Section: Discussionmentioning
confidence: 99%
“…No obstante, la asociación entre eventos deportivos y consumo de alcohol podría deberse a: las celebraciones con alcohol tras las victorias deportivas son frecuentes; o a la participación en competiciones conlleva a veces el viajar fuera del domicilio paterno, lo cual podría incrementar la probabilidad de consumos alcohólicos (Tahiraj et al, 2016). En cualquier caso, la asociación entre consumo de alcohol y deporte en jóvenes no está clara, con algunos estudios que encuentran que el consumo peligroso de alcohol es más frecuente en chicos que han participado mayor tiempo en deportes (OR = 1,49) (Sajber, Tahiraj, Zenic, Peric y Sekulic, 2016) y otros que muestran un efecto positivo del deporte en jóvenes que se concreta en menos consumo de alcohol (Lopez, Rodriguez, Garcia y Perez, 2016).…”
Section: Discussionunclassified